An empirical evaluation of the use of video films in training: A behaviouristic analysis - C. Viedge; P. A. Taffinder (South African Journal of Business Management, 1987)
Considerable organizational resources are expended annually on training, yet little empirical research is undertaken to investigate the problem of transfer of training to the workplace. Video films are an integral part of many training courses and it is critical to evaluate the efficacy of such films in developing the intended skills. Within the operant behaviouristic perspective, an ABAB reversal experiment was conducted during four business game periods of a training course. The experimental objective was to assess the impact of the principles presented in a training film on the decision-making behaviour of six managers from an engineering research/production facility. A cue-board summarizing the decision-making principles presented in the film was unobtrusively introduced during the two 'B' phases of the experiment. Frequencies of the target behaviour were recorded by two independent raters across all consecutive 'A' and 'B' experimental phases. No functional relationship was found between the use of the decision-making principles and the introduction of the cue-board. In other words, despite the use of a cue-board to prompt decision-making behaviour, no transfer of training from the video-film to the analogue working environment of the business game was observed. Some implications of these results for employing video films in training are discussed.
Keywords: 650